A Romance of Wastdale - Mason, A. E. W. (Alfred Edward Woodley), 1865-1948 (Salt Lake City, UT : Project Gutenberg, 2012)
"A Romance of Wastdale" by A. E. W. Mason is a novel published in 1895. Set in England's Lake District, it follows David Gordon, who returns to a climbing retreat days before his wedding to Kate Nugent. His arrival coincides with that of Austen Hawke, his estranged former companion and romantic rival. When Gordon discovers devastating secrets about Kate's past in India and Hawke's blackmail, idealism collides with betrayal on the precipitous mountain ledges, leading to fatal consequences. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Romance_of_Wastdale_(novel)
Release date is 2012-01-30
Produced by Charles Bowen, from page scans provided by the Web Archive
Keywords: Fiction